Changing nature of Pleistocene interglacials - is it recorded by paleosoils in Hungary (Central Europe)? - Varga, György (Hungarian Geographical Bulletin, 2015)
Based on stable isotope analyses of worldwide reference curves, it has long been apparent that duration, intensity and climatic conditions of Pleistocene interglacial periods were significantly diverse. As a consequence of negligible fresh, detrital material admixture during interglacials, the soil formation intensity and maturity of various kinds of past soils have been holding vital information on the environmental conditions at the time the soils formed. This, in turn, means that several physicochemical properties of soils allow us to reconstruct past climatic regimes. Loess-paleosol sequences in Hungary (Central Europe) provide insight into the cyclic nature of glacial-interglacial variations of the last 1 million years. The paleosoils have been recognized as the product of warmer and moister interglacials, when the (glacial) loess material was altered by chemical weathering and pedogenic processes. The gradual change from oldest red Mediterranean soils via forest and forest-steppe soils to steppe soils represents well the continuous decrease of chemical alteration of interglacial paleosoils determined by environmental factors and duration of soil formation. Pedogene units from MIS-21 to MIS-5 strata were analysed in the course of this study. Major element analyses were carried out to get a proper picture on the paleoenvironmental conditions. Geochemical transfer functions have been applied to derive mean annual precipitation and mean annual temperature. These kinds of quantitative data on past climate and the stratigraphic data allow us to fit our pedostratigraphic units into a global context. The present paper is aimed at providing new information on the various climatic and environmental characteristics of Pleistocene interglacial periods and soil forming processes.